Body as landscape, love as intoxication conceptual metaphors in the Song of songs - Gault, Brian P. ca. 20./21. Jh. (Atlanta SBL Press, 2019)
A lock with no key? Body metaphors in the Song of Songs -- Missing key: A conceptual-comparative approach -- I am: Poems of self-description -- Nature as erotica: Sexual euphemism and double-entendre -- Anatomy of a rose: Praise for the female body -- Outstanding among ten thousand: An ode to the male body -- Conclusions: Method, metaphor, beauty, and unity.
The Song of Songs contains some of the most exquisite yet enigmatic poetry in the Hebrew Bible. One of the chief difficulties in interpreting the Song's lyrics is the unusual imagery used to depict the lovers' bodies. Why is the maiden's hair compared to a flock of goats (4:1), the man's cheeks likened to garden beds of spice (5:13), and the eyes of both lovers described as doves (4:1, 5:12)? While scholars speculate on the significance of these symbols, a systematic inquiry into the Song's body metaphors is curiously absent. Based on insights from cognitive linguistics, this study incorporates biblical and comparative data to uncover the meaning of these metaphors, surveying literature in the eastern Mediterranean (and beyond) that shares a similar form (poetry) and theme (love). Gault examines the extent of universal themes and culturally specific variations within these literary works, thus shedding light on the perception of beauty in Israel and its relationship to surrounding cultures
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Criticism, interpretation, etc; Bible